Photophysics of 9, 9‐Dimethylacridan‐Substituted Phenylstyrylpyrimidines Exhibiting Long‐Lived Intramolecular Charge‐Transfer Fluorescence and Aggregation‐Induced Emission Characteristics. Issue 3 (8th December 2020) - Fecková, Michaela; Kalis, Ioannis Konstantinos; Roisnel, Thierry; le Poul, Pascal; Pytela, Oldřich; Klikar, Milan; Robin‐le Guen, Françoise; Bureš, Filip; Fakis, Mihalis; Achelle, Sylvain
Abstract: Six pyrimidine‐based push–pull systems substituted at positions C2 and C4/6 with phenylacridan and styryl moieties, employing methoxy or N, N ‐diphenylamino donors, have been designed and synthesized through cross‐coupling and Knoevenagel reactions. X‐ray analysis confirmed that the molecular structure featured the acridan moiety arranged perpendicularly to the residual π system. Photophysical studies revealed significant differences between the methoxy and N, N ‐diphenylamino chromophores. Solvatochromic studies revealed that the methoxy derivatives showed dual emission in polar solvents. Time‐resolved spectroscopy revealed that the higher energy band involved very fast (<80 ps) fluorescence, whereas the lower energy one included long components (≈30 ns) due to long‐lived intramolecular charge‐transfer fluorescence. In contrast to N, N ‐diphenylamino chromophores, the methoxy derivatives also showed aggregation‐induced emission in mixtures of THF/water, as well as dual emission in thin films, covering almost the whole visible spectrum with corresponding chromaticity coordinates not far from that of pure white light. These properties render the methoxy derivatives as very promising organic materials for white organic light‐emitting diodes. Abstract : Doubling up : Six pyrimidine‐based push–pull systems substituted at positions C2 and C4/6 with phenylacridan and styryl moieties, employing methoxy or N, N ‐diphenylamino donors, are investigated. These chromophores show aggregation‐induced emission, as well as dual emission in polar solvents and in thin films, leading to white‐light emission.